Probing the Third Dimension of the Reef Complex at Kepulauan Seribu: A Proposal for Gathering Seismic Profiles and Cores of Holocene Sediments - Berita Sedimentologi (Ikatan Ahli Geologi Indonesia, 1998)
Integrated Data Services, Louisiana State University, and PT. Geoservices jointly announce their program of shooting shallow, high-resolution seismic profiles and trying these profiles with cores across the Kepulauan Seribu reef complex in the West Java Sea. The surface sediments of Kepulauan Seribu, 50 kilometers north of Jakarta, have been mapped in considerable detail; in addition, a few cores have been taken in shallow water reef environment. However, no deep-water coring nor shallow seismic data has been gathered to investigate the evolution of this modern reef complex. In fact, Holocene reef facies here sit atop equivalent Miocene Reef facies which produce at the giant Bima Field.This research program will gather a series of seismic profiles and take several cores along these profiles. All representative environments of deposition will be sampled with these techniques, including shallow- and deep-water settings. Companies are asked to participate in this program by taking part in data collection, in the sharing of samples, and in the funding of operational costs. A final report by the principal investigators will be distributed to participant companies.